Activation of CXCL12-CXCR4 signalling induces conversion of immortalised embryonic kidney cells into cancer stem-like cells. Issue 1 (1st January 2020) - Oh, Seung-ick; Jeong, Hyesun; Park, Hang-soo; Choi, Kyung-Ah; Hwang, Insik; Lee, Jiyun; Cho, Jeonghee; Hong, Sunghoi
Abstract: Cancer stem cells (CSCs) have been implicated in the growth and progression of several types of human cancer. The technology to derive and establish CSCs in vitro could be a critical tool for understanding cancer and developing new therapeutic targets. In this study, we derived expandable CD15 + induced CSCs (iCSCs) from immortalised 293FT human epithelial cells by co-culture with human bone marrow-derived mesenchymal stem cells (BM-MSCs) as feeder cells in vitro . The iCSCs converted through an epithelial-mesenchymal transition program acquired mesenchymal traits, the expression of stem cell markers, and epigenetic changes. Moreover, the iCSCs not only efficiently formed tumorspheres in vitro but also initiated tumours in immunocompromised mice injected with only 10 of the iCSCs. Furthermore, we showed that the expression of the chemokine CXCL12 and its receptor CXCR4 by the iCSCs resulted in the activation of the Fut4 gene through CXCR4/ERK/ELK-1-signalling pathways and the maintenance of the iCSCs in the undifferentiated state through CXCR4/AKT/STAT3-signalling. These findings suggest that immortalised 293FT cells may acquire potential oncogenicity through molecular and cellular alteration processes in microenvironments using BM-MSCs, and could represent a valuable in vitro model as a cancer stem cell surrogate for studying the pathophysiological properties of CSCs.